2011
DOI: 10.1007/s11837-011-0182-3
|View full text |Cite
|
Sign up to set email alerts
|

Reducing impurities of multicrystalline silicon in a unidirectional solidification furnace for solar cells

Abstract: How would you……describe the overall significance of this paper? This paper proposed some methods to reduce the impurities of carbon and oxygen during the production of multicrystalline silicon. Therefore, high-quality and high-efficiency multicrystalline silicon can be obtained by the present solutions.…describe this work to a materials science and engineering professional with no experience in your technical specialty? We theoretically analyzed the incorporation mechanism of impurities of carbon and oxygen, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Impurities such as oxygen, carbon, and metals will be inevitably introduced during directional solidification in silicon. The content of impurities effects seriously on the generation of defects such as dislocations in silicon ingot [2,3]. Controlling the content of impurities in the polysilicon can improve the properties of the silicon wafers [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impurities such as oxygen, carbon, and metals will be inevitably introduced during directional solidification in silicon. The content of impurities effects seriously on the generation of defects such as dislocations in silicon ingot [2,3]. Controlling the content of impurities in the polysilicon can improve the properties of the silicon wafers [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…The content of impurities effects seriously on the generation of defects such as dislocations in silicon ingot [2,3]. Controlling the content of impurities in the polysilicon can improve the properties of the silicon wafers [2,4]. Recently, lots of studies have indicated that optimizing the solidification process can reduce the impurity in polysilicon [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the casting of multicrystalline Si (mc-Si) ingots for solar cells, metallic impurities, oxygen, and carbon are incorporated into the ingot from the crucible, which is usually coated with Si 3 N 4 powder, and from the atmosphere [1][2][3][4][5][6][7][8][9]. If low-grade raw materials, also called metallurgical silicon or solar-grade silicon, are used for the growth, a variety of metallic impurities will be present in the melt.…”
mentioning
confidence: 99%